Konsep desain taman terapi paru di Rumah Sakit Paru Dungus, Kabupaten Madiun, Provinsi Jawa Timur - Asmi, Dwi Ulul; Kohdrata, Naniek; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2019)
The lung therapeutic garden conceptual design at Dungus Lung Hospital at Madiun Regency East Java Province. Dungus Lung Hospital of Madiun Regency is a health care center that treats patients who have respiratory disease and general illnesses. An approach that can be given to help healing process of respiratory disease is the psychological and physiological through of The Lung Therapeutic Garden. The therapeutic garden uses concepts and elements of a garden appropriate for respiratory distress therapy. The concept applies to The Lung Therapeutic Garden is healing environment by applying garden elements such a natural hardscape like a rocks and woods, and softscape like water and colored plants, textured plants, and fresh scent flowering plants. The Lung Therapeutic Garden at Dungus Lung Hospital is based on Marcus’ therapeutic rationale. The aims of this study is to design a lung therapeutic garden. The method used in this research was field survey based on Rachman’s complete thinking process (1984). Furthermore, this research data will be aligned with the Time Saver Standards for Landscape Architecture in planning and designing The Lung Therapeutic Garden. The result of this study is the concept of healing environment that suitable to be applied to help healing process of respiratory distress. This is according to patient’s need for clean air with adequate oxygen concentration and sunlight. The application of natural hardscape and softscape as objects of therapy can assist the healing process by stimulating human senses.